Tindakan Radikal sebagai Bentuk Penolakan Politik Seksual dalam Naskah Drama Re-: Radical Action as a Form of Rejection of Sexual Politics in the Drama Script “Re-” - Rinda Widya Ikomah; Ismail Marzuki; Mustakim Saleh (Universitas Tidar, 2026)
This study highlights the patriarchal power relations in Fachri Mahayupa's drama script Re- and the radical actions of female characters to eliminate sexual politics that place women in a subordinate position. The problem studied is how male domination is embedded in social structures and dramatic practices, as well as women's strategies to challenge it. The purpose of this study is to understand the radical actions of female characters in dismantling patriarchal power relations and upholding gender equality. The research method is qualitative descriptive-analytical, using dramatic text analysis to examine dialogues, monologues, narratives, and symbols that depict patriarchal domination and women's responses to it, within the framework of Kate Millett's sexual politics theory and radical feminism. The results show that female characters in the script systematically take over masculine roles, build courage, and instill anti-domination values, including efforts to completely eliminate male power through symbolic and dramatic actions, although their radical actions are not entirely successful. Another finding, the Re- manuscript emphasizes the importance of the concept of androgynous humans who integrate positive masculine and feminine traits, as an effort to create gender equality and social harmony, while also emphasizing that resistance to patriarchy is not only challenging male dominance, but also building balance and autonomy for all individuals.